Dampak Penyaluran Bantuan Program Keluarga Harapan Terhadap Kemandirian Rumah Tangga Di Desa Plosojenar 2016-2022 - Muhammad Heru Akhmadi; Nurul Khilyati; Erlita Nurma Wati (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2023)
Social assistance named conditional cash transfer (PKH) is a program that administered by the government in overcoming extreme poverty. This study aims to determine and analyze the impact and effectiveness of the distribution of the PKH in Plosojenar Village, Pati Regency, Central Java from 2016-2020. This research using qualitative methods with a case study approach where data collection was obtained from literature studies and interviewees and using ATLAS.ti software to analyze the data. The results showed that the process of distributing PKH social assistance in Plosojenar Village was in accordance with the technical guidelines for the PKH social assistance distribution set by the government. From 2016 to 2020, there were 57 poor people who received the PKH social assistance, known as beneficiary families (KPM). Of the 57 KPM, there were 4 KPM who left the KPM because they had died. The distribution of the PKH social assistance has been running effectively, marked by better indicators of the lives of the poor in terms of health, education, and social welfare. The government should continue the process of distributing social assistance to the PKH in the context of alleviating extreme poverty in the community. In addition, in order to achieve household independence, guidance from PKH facilitators is needed so that KPM can use social assistance to improve their standard of living.